Teknik Komputer Mengabdi : Pelatihan Komputer Di Yayasan Bina Insani Al Muhyin Naba Pringgasela - Akbar, Taufik; Nuzuluddin, Muhammad; Putra, Hadian Mandala; Ahmadi, Ahwan; 'Alimudin, 'Alimudin; Dewi Patwari, Intan Komala (Jurnal Teknologi Informasi untuk Masyarakat, 2023)
The computer training at the Bina Insani Al Muhyin Naba' Foundation in the village of Pringgasela is a strategic effort to enhance digital literacy and technological skills among students at the junior high school level. This program discusses the implementation of computer training as an initiative to equip students with a profound understanding of computer usage and the latest technology. The training aims to prepare students for the digital era, provide equal access to educational opportunities, and stimulate local economic development. Through an integrated curriculum and active participation from stakeholders, computer training at the Bina Insani Al Muhyin Naba' Foundation in the village of Pringgasela creates an inclusive and sustainable learning environment. Evaluation results show a significant improvement in students' digital literacy, which is expected to contribute to their readiness to face the demands of an increasingly digitally connected society. By combining formal education approaches and community development, this computer training has the potential to create positive impacts not only within the school environment but also in enhancing the overall quality of life and economic potential of the Pringgasela community.